PENERAPAN KONVENSI IMDG CODE DALAM PENANGANAN BARANG PADA PETI KEMAS DANGEROUS GOOD KELAS 1 DAN KELAS 7 DI PT JAKARTA INTERNASIONAL TERMINAL - Rudy Max Damara Gugat; Devi Widia Putri; Tjetjep Karsafman (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
This study refutes the procedures for transporting dangerous class 1 and 7 goods from trailers or ships to stacking fields and vice versa at Tanjung Priok Port Container I Terminal, and compares the procedures for moving containers, dangerous goods, classes 1 and 7 used by loading and unloading companies load I Container Port of Tanjung Priok Port with the IMDG convention code, 2004, specifically during fires and leaks. The main problem in this study is which one can change the IMDG code that has been applied in the transfer of containers containing dangerous goods class 1 and 7. This study uses a descriptive comparative method. The results of the study concluded that the application of trucks directly lost and directly loaded trucks could lead to accidents or recovery in the field. Implementation of the separation system regulations in accordance with the IMDG Code regulations, but still found inadequate personal protective equipment facilities such as breathing apparatus, safety gloves, ear plugs, face and eye protection equipment.